Consumption of ultra-processed foods and metabolic syndrome in adolescents: a systematic review protocol - Lima, Luiz Eduardo Rodrigues (2022)
Objective: This protocol will describe the methods of a systematic review that examined studies on the relationship between consumption of ultra-processed foods and metabolic syndrome in adolescents. Methods: The searches will be carried out in the MEDLINE (via PubMed), EMBASE (via ScienceDirect), LILACS (via VHL), and Cochrane databases until March 2022. Observational (cohort, case-control and cross-sectional) and experimental (clinical trials) studies will be included, two researchers’ independents will use the Rayyan QCRI software for retrieval of the articles, in addition, the Mendeley software Reference Manager will be used for reference management. After reading them in full, the articles will be selected according to the eligibility criteria. Results: The synthesis of evidence data will be approached from the relationship of consumption of ultra-processed foods and metabolic syndrome in adolescents. Conclusion: Therefore, the importance of this review protocol is highlighted to compose the current evidence on the relationship between consumption of ultra-processed foods and the metabolic syndrome.